BUKU SAKU BAHASA ARAB BERBASIS METODE KOMUNIKATIF UNTUK MENINGKATKAN KUALITAS MAHAROH KALAM - Amrini Shofiyani; Siti Khoirotun Nisa (Jurnal Education and Development, 2023)
Arabic in the world of education occupies a very backward position in education circles in Indonesia. This is very inversely proportional to the position of Arabic in the pesantren environment, they put learning Arabic ahead of others, this superior position makes Arabic more known and considered important due to the existence of books in Arabic, making it a very important learning. important to them. Arabic language education at Denanyar Arabic and English language institutions requires its students to be able to speak Arabic well. This is a big problem for those students who before entering LBAI did not know Arabic at all. So this is where I as a researcher created a pocket book based on communicative methods which I hope can become a guide for students so that they can further improve the quality of their speaking